Clinicopathological study of oral submucosal fibrosis androle of steroid, benzoic acid and salicylic acid alone or in combination therapy - Kumar, Ramesh; Lal, Deepchand; Bishnoi, Suman; Nagraj, Niranjan; Gupta, Gavrav; Samor, Vivek (International Surgery Journal, 2016)
Background:Oral submucosal fibrosis is a potentially malignant disease. This study aims to compare the efficacy of corticosteroid, benzoic acid, salicylic acid alone or in combination therapy for the treatment of oral submucous fibrosis and to analyse the histopathology of biopsied samples from all patients. Methods: This study was conducted at Sardar Patel medical College from 2014 to 2015. Corticosteroids locally and in combination of oral administration. Group II was treated with 4% salicylic acid alone and in combination of 4% benzoic acid. The last group III was treated with both the drug used in Group I and II. All the collected biopsy specimen was stained by haematoxilin and eosin stain. All collected data was tabulated and stastically analyzed by using SPSS software. Results:The common presenting symptoms were intolerance to spicy food. A mild to moderate improvement was observed in symptomatology and physical findings in majority of cases of Group I A. The magnitude of the improvement was, however, found to be more in patients of Group IB. A moderate to marked improvement was observed in patients of Group II. The magnitude of improvement was better in II B to II A Group. The improvement in symptomatology and physical findings was found to be much more marked in patients of Group III treated with combination therapy. Conclusions:Oral submucosal fibrosis is a premalignant condition. Early recognition and treatment is necessary. Therapy with keratolytic agents along with local infiltration of corticosteroids helps in improvement of the condition.